Case report: Urgent liver pathologies: All in one - Pavlek, Goran; Romic, Ivan; Juzbasic, Kristina; Alduk, Ana Marija; Petrovic, Igor; Radojkovic, Rudolf; Grbavac, Dario; Silovski, Hrvoje (Frontiers in Surgery, 2022)
Ruptured hepatocellular carcinoma is a well-known serious complication of this most common primary liver malignancy. However, when HCC rupture is associated with other liver focal lesions the diagnosis and therapy may be very challenging. We report a unique case of HCC rupture complicated with liver abscess, hematoma and portal vein thrombosis.